The efficacy of dietary therapies in modulating inflammatory biomarkers, clinical remission and quality of life in patients with inflammatory bowel disease: a network meta-analysis of 15 interventions - Wei, Kexi; Li, Min; Zhao, Yuqing (Frontiers in Nutrition, 2025)
BackgroundScientific dietary interventions are useful methods for managing inflammatory bowel disease. It is unclear which dietary pattern is most effective in improving IBD symptoms. Therefore, this network meta-analysis compared the impact of popular dietary patterns on patients with established IBD.MethodsA computerized search of randomized controlled trials on the use of dietary therapy to improve inflammatory bowel disease in both Chinese and English databases. The primary outcome measures were CRP, ALB, IBDQ and MES. Stata 16.0 software was used for the network meta-analysis.ResultsA total of 25 RCTs were ultimately included. The study included the following 15 treatments. The network meta-analysis revealed that, for reducing CRP levels, LFD + EN was significantly more effective than LRD [MD = −5.21 mg/L, 95% CI (−7.05, −3.36)], RD [MD = −4.63 mg/L, 95% CI (−6.22, −3.03)], CDED + EN [MD = −4.48 mg/L, 95% CI (−7.45, −1.51)], LFD [MD = −4.47 mg/L, 95% CI (−6.27, −2.67)], MD + LFD + EN [MD = −3.68 mg/L, 95% CI (−5.90, −1.45)] and EN [MD = −1.26 mg/L, 95% CI (−2.29, −0.22)]. Conversely, LFD + EN was also superior in increasing ALB levels when compared to EN [MD = 3.64 g/L, 95% CI (0.71, 6.57)], LFD [MD = 6.35 g/L, 95% CI (2.85, 9.84)], RD [MD = 6.40 g/L, 95% CI (3.25, 9.54)], LRD [MD = 6.34 g/L, 95% CI (2.83, 9.84)], MD [MD = 6.34 g/L, 95% CI (2.83, 9.84)], CDED + EN [MD = 8.40 g/L, 95% CI (4.18, 12.61)] and lgG-ED [MD = 8.73 g/L, 95% CI (4.34, 13.11)]. Regarding MES, lgG-ED [SMD = 1.07, 95% CI (0.64, 1.50)], LFD [SMD = 0.75, 95% CI (0.48, 1.03)], EN [SMD = 0.64, 95% CI (0.27, 1.01)] all demonstrated a significant reduction in scores compared to RD. No significant difference was found in IBDQ.ConclusionFor reducing systemic inflammation (CRP, ALB), LFD + EN was ranked as the most effective strategy. For improving quality of life (IBDQ), MD + LFD + EN showed the highest probability of being the best. For inducing endoscopic remission (MES), IgG-ED was ranked highest among the compared interventions. In the future, evidence-based dietary interventions could be used in clinical practice.Systematic review registrationhttps://www.crd.york.ac.uk/PROSPERO/view/CRD420251038185.